Architect Nina Anatolievna Rumyantseva (10.12.1916 – 16.11.2007) - Druzhinina, Inna (project baikal, 2023)
The article is devoted to the biography and creative work of the Soviet architect Nina Anatolievna Rumyantseva. Nina Anatolievna’s life and creative path are related to a significant geography of places – from Kazakhstan, Western and Eastern Siberia to the Far East and the capital of the country, which can be considered a vivid reflection of the specifics of the Soviet time. The years of her creative activity, particularly in Irkutsk, fell on the late 1940s – early 1970s and coincided with the period of intensive development of Eastern Siberia. For the first time the pages of N. A. Rumyantseva’s life and a detailed list of her works are presented in the most complete way. The material is based on documents from the archive of the Irkutsk regional organisation of the Union of Architects, on personal recollections of Nina Anatolievna and her colleagues.